Corrections of some errors in the paper “Molecular delineation of the Agave Red Worm Comadia redtenbacheri (Lepidoptera: Cossidae)”. Zootaxa, 4375 (3), 358–370 - Cárdenas-Aquino, María Del Rosario; Alarcón-Rodríguez, Norma Marina; Rivas-Medrano, Mario; González-Hernández, Héctor; Vargas-Hernández, Mateo; Sánchez-Arroyo, Hussein; Llanderal-Cázares, Celina (Zootaxa, 2019)
N/A